2018
DOI: 10.1590/0101-60830000000154
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based psychotherapy for treatment of anorexia nervosa in children and adolescents: systematic review

Abstract: Background: Efficacy studies on the treatment of anorexia nervosa (AN) in childhood and adolescence are scarce and systematic reviews are almost non-existent. Objective: Systematic review of the literature regarding the modalities of psychological intervention based on evidence used in the treatment of AN in childhood and adolescence. Methods: The research was carried out in the databases: PubMed, PsycINFO and Cochrane, using the combined keywords: anorexia nervosa and evidence-based therapy. Articles publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Additionally, there is a consensus that despite a growing evidence-base for treatments for anorexia and a preference for psychotherapy as treatment, there still remains no established leading treatment [9,80]. A number of treatment reviews conclude that among a variety of psychotherapies, including the aforementioned treatments recommended by the NICE guidelines, there is no convincing evidence to suggest one consistently superior intervention for treating adults, children or adolescents with anorexia nervosa [44,50,69,81]. This is largely due to the difficulty of trialling treatments for anorexia because of difficulty recruiting participants, high rates of patient drop-out or non-adherence to treatment and withdrawal from clinicians as a result of risk not being stabilised [50].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there is a consensus that despite a growing evidence-base for treatments for anorexia and a preference for psychotherapy as treatment, there still remains no established leading treatment [9,80]. A number of treatment reviews conclude that among a variety of psychotherapies, including the aforementioned treatments recommended by the NICE guidelines, there is no convincing evidence to suggest one consistently superior intervention for treating adults, children or adolescents with anorexia nervosa [44,50,69,81]. This is largely due to the difficulty of trialling treatments for anorexia because of difficulty recruiting participants, high rates of patient drop-out or non-adherence to treatment and withdrawal from clinicians as a result of risk not being stabilised [50].…”
Section: Resultsmentioning
confidence: 99%
“…This is largely due to the difficulty of trialling treatments for anorexia because of difficulty recruiting participants, high rates of patient drop-out or non-adherence to treatment and withdrawal from clinicians as a result of risk not being stabilised [50]. Still, psychotherapies that include the family seem to be more promising and tentatively deemed most appropriate and preferred in the treatment of children and adolescents with anorexia [81].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature indicates that parents' participation in the treatment of their children with Anorexia Nervosa (AN) is associated with better prognosis 1 . In family-based treatment 2 , the most tested form of psychotherapy for AN in childhood and adolescence, parents are protagonists in the behavioral management for weight recovery and control of symptoms 3 .…”
Section: Dear Editormentioning
confidence: 99%
“…A recent systematic review 3 indicated that the most tested model of treatment in childhood and adolescence is family-based therapy (FBT) 4 , which is recommended by the international reference guidelines in mental health, such as those of the National Institute for Health and Clinical Excellence 5 . However, even this treatment modality may not be adequate for all families or patients 5 and the results are considered to be modest 3 . The authors of the study consider further studies to be needed due to the scarcity of clinical trials, the methodological weaknesses and the different designs tested.…”
Section: Introductionmentioning
confidence: 99%